2010
DOI: 10.1152/ajprenal.00738.2009
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal suppression of angiotensin II type 1 receptor binding molecule in angiotensin II-infused mice

Abstract: ATRAP [ANG II type 1 receptor (AT1R)-associated protein] is a molecule which directly interacts with AT1R and inhibits AT1R signaling. The aim of this study was to examine the effects of continuous ANG II infusion on the intrarenal expression and distribution of ATRAP and to determine the role of AT1R signaling in mediating these effects. C57BL/6 male mice were subjected to vehicle or ANG II infusions at doses of 200, 1,000, or 2,500 ng·kg(-1)·min(-1) for 14 days. ANG II infusion caused significant suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 51 publications
3
36
2
1
Order By: Relevance
“…Numerous studies have shown that alterations in AT1 expression leading to altered regulation of downstream intracellular modulators dictate specific patterns in downstream effectors; however, the role of these intracellular modulators on AT1 transcription remains enigmatic (Bonde et al 2010, Wakui et al 2010, Ozawa et al 2011. In this study, we examined the effect of 13cRA on the expression of AT1 in rat liver epithelial cells known to express the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that alterations in AT1 expression leading to altered regulation of downstream intracellular modulators dictate specific patterns in downstream effectors; however, the role of these intracellular modulators on AT1 transcription remains enigmatic (Bonde et al 2010, Wakui et al 2010, Ozawa et al 2011. In this study, we examined the effect of 13cRA on the expression of AT1 in rat liver epithelial cells known to express the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization and specificity of the anti-ATRAP antibody and the anti-AT1R antibody (sc-1173; Santa Cruz Biotechnology Inc., Santa Cruz, California, USA) were described previously [19,20,25,26]. The antip22phox antibody (sc-20781; Santa Cruz Biotechnology Inc.), anti-p47phox antibody (sc-14015; Santa Cruz Biotechnology, Inc.), anti-Rac1 antibody (DAM1522857; Millipore) and anti-Ang II type 2 receptor (AT2R) antibody (sc-9040; Santa Cruz Biotechnology Inc.) were also used in this study.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The antip22phox antibody (sc-20781; Santa Cruz Biotechnology Inc.), anti-p47phox antibody (sc-14015; Santa Cruz Biotechnology, Inc.), anti-Rac1 antibody (DAM1522857; Millipore) and anti-Ang II type 2 receptor (AT2R) antibody (sc-9040; Santa Cruz Biotechnology Inc.) were also used in this study. Western blot analysis was performed essentially as described [19,20,25,26].…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies also revealed that there was significant suppression of endogenous ATRAP expression in the renal inner cortex and outer medulla concomitant with the development of Ang II-mediated hypertension and salt-sensitive hypertension. 19,20 A previous study showed that as SHR-SP rats developed hypertension, the genes encoding components of the reninangiotensin system were expressed at higher levels in the kidney 21 ; therefore, it was proposed that the intrarenal reninangiotensin system is activated by this type of genetic hypertension. Thus, further investigations are warranted to examine the possible role of renal ATRAP in the pathophysiology of hypertension and renal injury, including albuminuria and the production of oxidative stress-related molecules, in SHR-SP rats (Figure 1).…”
mentioning
confidence: 99%